2017
DOI: 10.1155/2017/2752716
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Nemopilema nomurai Jellyfish Venom on HepG2 Cells and a Tumor Xenograft Animal Model

Abstract: Various kinds of animal venoms and their components have been widely studied for potential therapeutic applications. This study evaluated whether Nemopilema nomurai jellyfish venom (NnV) has anticancer activity. NnV strongly induced cytotoxicity of HepG2 cells through apoptotic cell death, as demonstrated by alterations of chromatic morphology, activation of procaspase-3, and an increase in the Bax/Bcl-2 ratio. Furthermore, NnV inhibited the phosphorylation of PI3K, PDK1, Akt, mTOR, p70S6K, and 4EBP1, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 48 publications
5
25
0
Order By: Relevance
“…Our previous study for the first time showed that NnV suppresses hepatic tumour growth both in vitr o and in viv o 31 . Especially, tumour tissues in NnV-treated animals were less diffuse (more compact) and showed stronger E-cadherin expression than non-treated animals.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous study for the first time showed that NnV suppresses hepatic tumour growth both in vitr o and in viv o 31 . Especially, tumour tissues in NnV-treated animals were less diffuse (more compact) and showed stronger E-cadherin expression than non-treated animals.…”
Section: Discussionmentioning
confidence: 91%
“…Jellyfish venom is composed of various molecules including peptides, enzymes, neurotoxin, cytolysin, haemolysin with biological effects 38 46 . According to our previous study on the anti-cancer effect of NnV, metalloprotease component in NnV might be the main component contributing to apoptotic HepG2 cell death 31 . In support of this notion, other venoms (of snakes and spiders) also have metalloprotease activities that inhibit cell adhesion, proliferation, migration, invasion, and angiogenesis 47 50 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Crude venom from Nemopilema nomurai had cytotoxic and cytolytic effects on heart and muscle myoblasts in mice and blood cells from different organisms, including humans [112]. More recently, an anti-tumoral activity was assessed in a model animal for extracts of crude venom from the same species [158]. Cyanea nozakii crude venom was toxic for colon cancer and hepatoma cells in humans [159].…”
Section: Biotechnological Applications Of Scyphomedusae: State Of mentioning
confidence: 99%
“…Jellyfish glycoprotein qniumucin can prevent articular cartilage degeneration in in vivo studies using an osteoarthritis (OA) model [ 27 ]. Our most recent report demonstrated that NnV exerts highly selective cytotoxicity in HepG2 cells via dual inhibition of the Akt and mTOR signaling pathways, but normal cells remained unaffected [ 28 ]. In the present work, we have analyzed the potential therapeutic targets of NnV at the proteomic level for the first time.…”
Section: Introductionmentioning
confidence: 99%